Invoking the Prophet Muhammad through Word, Sound, and Image - Blair, Sheila (Religion and the arts, 2016)
Objects associated with the practice of the Muslim faith are often inscribed with Qurʾanic verses specifically chosen to reflect their spiritual functions and project the piety of the patrons who ordered them and the believers who used them. This essay focuses on one such Qurʾanic passage: the invocation of the Prophet Muhammad in Qurʾan 33: 56, a verse saying that God and His angels bless the Prophet and that believers should bless him too and give him greetings of peace. The article analyses the use of this verse on buildings and objects of various media in five different places from early Islamic to pre-modern times to show how words, sounds, and images could be used to elaborate different aspects of Muhammad’s persona, ranging from his unique position as beautiful model to his roles as intercessor, miracle-worker, and protagonist in the miraculous night journey and ascension.